1996
DOI: 10.2527/1996.741138x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gilt age and body composition at first breeding on sow reproductive performance and longevity.

Abstract: Regression analysis was used to evaluate the effects of gilt age and body composition at first breeding on sow performance over three parities. Eighty-seven Yorkshire x Landrace F1 gilts were used. Variation in age and body composition at first breeding was obtained by breeding gilts at puberty, second, or third estrus and by providing those gilts bred after puberty one of four nutritional regimens from puberty until breeding: 1) 2.7 kg/d of a 14.3% CP, 3.5 Mcal ME/kg diet (H), 2) maintenance ME and CP/d (M), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
3
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 22 publications
2
45
3
3
Order By: Relevance
“…This observation is not consistent with reports showing positive effects in parity 1 and/or 2 sows [1,9]. However, the range of age at first conception in our study was older (10 and 90 percentiles: 227 to 322 days) than in previous studies that used relatively young age ranges between 180 and 245 days [1], 200 and 280 days [9], and 138 and 279 days [7]. It is possible that age at first conception within the relatively old ages (approximately 230 to 320 days) does not affect litter size at parity 1 because ovaries and uterus have been developed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This observation is not consistent with reports showing positive effects in parity 1 and/or 2 sows [1,9]. However, the range of age at first conception in our study was older (10 and 90 percentiles: 227 to 322 days) than in previous studies that used relatively young age ranges between 180 and 245 days [1], 200 and 280 days [9], and 138 and 279 days [7]. It is possible that age at first conception within the relatively old ages (approximately 230 to 320 days) does not affect litter size at parity 1 because ovaries and uterus have been developed.…”
Section: Discussioncontrasting
confidence: 99%
“…Age at first conception is a possible factor affecting longevity [7] and lifetime pig production. Previous research on age at first mating has not examined farrowing rate at parity 0 (gilts).…”
mentioning
confidence: 99%
“…Piglet weights at birth and at weaning and ADG in this study are similar (Johansen et al, 2004) or slightly higher (Rozeboom et al, 1996;Quiniou et al, 2002;Deen and Bilkei, 2004) than values reported in other studies. Moreover, fostering strategies could lead not only to lower pre-weaning mortality, but also to higher daily gain in litters with similar BW (Deen and Bilkei, 2004).…”
Section: Discussioncontrasting
confidence: 55%
“…As a result, gilts retrieving the feed continue to use the feed for stock collection and use fat reserves as a source of components necessary for the production of milk. Rozeboom et al (1996) suggested that the weaker pregnancy anabolism probably slows lactation in sows, which may result in the reduction of the number of piglets weaned, as a result of the insufficient production of milk. Holm et al (2004) found that the backfat thickness, which is considered a source of energy for sows, may also have an important role in the subsequent reproductive cycles.…”
Section: Discussionmentioning
confidence: 99%